BiOX (X = Cl, Br, and I) Nanoplates Prepared by Surfactant-Free Microwave Synthesis and Their Photocatalytic Performance - Panudda Patiphatpanya (2018)
© 2018, Pleiades Publishing, Ltd. Abstract: Bismuth oxyhalide (BiOX; X = Cl, Br, and I) nanoplates were successfully synthesized by microwave irradiation of surfactant-free aqueous solutions. X-rays diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed the presence of pure tetragonal BiOX (X = Cl, Br, and I) nanoplates. Photocatalytic activity of BiOX nanoplates was studied in visible light photodegradation of methyl orange (MO) as model dye. In this research, the photocatalytic efficiencies of BiOBr, BiOCl, and BiOI in photodegradation of MO induced by visible light within 300 min were 87.2, 73.1, and 69.7% and were higher than that of TiO2 Degussa P25 (29.2%).